Uji Iritasi Gel Ekstrak Etanol Herba Pegagan (Centella Asiatica L ) Dengan Gelling Agent Carbopol 940 - Tama Octi R. Ramli; Mazaya Fadhila (Program Studi DIII Farmasi Akademi Farmasi Dwi Farma, 2022)
Gel is a form of cosmetics, before being marketed cosmetics must pass a safety test. The safety test can be carried out using the patch test method, in which the test substance is attached to normal skin, then covered and carried out for 24 hours. Herb gotu kola has the property of accelerating wound healing. Centella asiatica herb extract was prepared by maceration method with 96% ethanol as a solvent and formulated in gel form using carbopol as a gelling agent. The preparations were made into 2 formulas with a ratio of formula 1 without extract and formula 2 using 12.5 mg extract. The irritation test was carried out on 20 volunteers consisting of men and women aged 20-35 years, each of which was attached to the test material formula 1 and formula 2. The test material was affixed for 4 hours to the upper arm of the volunteer closed and observed at 24 hours , 48, 72 hours after the test substance was released and the degree of irritation was calculated. All the test materials from the irritation test obtained a degree of irritation score of 0 which means that all the test ingredients are not irritating.